2022
DOI: 10.1128/msystems.00243-22
|View full text |Cite
|
Sign up to set email alerts
|

Early Introduction of Plant Polysaccharides Drives the Establishment of Rabbit Gut Bacterial Ecosystems and the Acquisition of Microbial Functions

Abstract: Our study was designed to gain a better understanding of how different feeding patterns affect the dynamics of gut microbiomes and microbe–host interactions. This research showed that the timing of solid food introduction is a key component of the gut microbiota shaping in early developmental stages, though with lower impact on settled gut microbiota profiles in older individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Beaumont et al [ 29 ] found that the relative concentrations of acetate, butyrate, propionate, glucose, and glutamate in the intestines of juvenile rabbits increased with age and the relative abundance of Firmicutes increased with age. Charlotte et al [ 30 ] demonstrated that very early ingestion of solid food in infant rabbits, although in small quantities, induced changes in gut microbiota colonization and activity, with an acceleration of the ecological species succession and increased production of short-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Beaumont et al [ 29 ] found that the relative concentrations of acetate, butyrate, propionate, glucose, and glutamate in the intestines of juvenile rabbits increased with age and the relative abundance of Firmicutes increased with age. Charlotte et al [ 30 ] demonstrated that very early ingestion of solid food in infant rabbits, although in small quantities, induced changes in gut microbiota colonization and activity, with an acceleration of the ecological species succession and increased production of short-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, nonrumination herbivores (e.g., horse, donkey, and rabbit) showed significantly different stomach microbiota compositions during the development, as enzyme-based chemical and fermentative digestions were found in the stomach of nonruminants and ruminants, respectively. Actually, the cecum and gut seem to be more important in the studies of nonruminants, for example, rabbits (Paës et al 2022). Previous studies have shown that Firmicutes and Bacteroidetes were the dominant microbes in the stomach or rumen of adult herbivores (Supplemental Table S49; Jin et al 2018;Guo et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…1 and 7-day old piglets, vs those that did have access, i.e. 28, 36 and 180-day old pigs, assuming that the luminal environment would differ [17,18]. Interestingly, the percentage of organoids to spheroids in the primary culture was greater for organoids originating from younger pigs that did not had access to solid feed than older ones that did (Fig 3D ) and this ratio was maintained with increasing number of passages (Fig 3F and G).…”
Section: Donor Age Influenced Organoid Growthmentioning
confidence: 99%